2015
DOI: 10.1080/09715010.2015.1067575
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater level fluctuation by using remote sensing and GIS in West Bokaro coalfield, Jharkhand, India

Abstract: West Bokaro coalfield is mostly affected by active mining industries and faces acute shortage of portable surface water and thus, people are very much dependent on groundwater. The objective of this paper is to assess the parameters which have significant impact on groundwater level fluctuation in West Bokaro coalfield by using remote sensing, GIS, and field-based water level data for two seasons. The objective is achieved by preparation of thematic maps of parameters which have significant impact on groundwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 14 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Zernitz et al, [36] has described details about drainage patterns and their significance importance. Drainage can play a significant role in any area′s water resources management [21,37,38]. Chowdhury et al, [39] suggested that drainage density can indirectly reveal the suitability for groundwater recharge of any area due to its association by surface runoff and permeability.…”
Section: Drainage Systemsmentioning
confidence: 99%
“…Zernitz et al, [36] has described details about drainage patterns and their significance importance. Drainage can play a significant role in any area′s water resources management [21,37,38]. Chowdhury et al, [39] suggested that drainage density can indirectly reveal the suitability for groundwater recharge of any area due to its association by surface runoff and permeability.…”
Section: Drainage Systemsmentioning
confidence: 99%
“…There are many studies in the literature about the measurement of changes in the groundwater resources with GIS. GIS is used in reviewing the quality and pollution of groundwater created by a particular agricultural production preference and urban land use changes in the urban area (Babiker et al 2004, Almasri and Kaluarachchi 2004, Nas and Berktay 2010, Krishnaraj et al 2015, the determination of groundwater levels and fluctuations and the mapping of protected areas in general (Jha et al 2010, Başçiftçi et al 2013, Chandra et al 2015, Tiwari et al 2016, Chandan and Yashwant 2017, Arya et al 2018, Çelik and Hamidi 2018, Çıldır et al 2019, Anand et al 2020, in the examination of groundwater level changes arising due to use and land cover change in special areas such as agricultural areas (Dinka et al 2013, Çelik et al 2016, Balasubramani et al 2019 and the development of a three-dimensional groundwater flow model (Gossel et al 2004). GIS is an important tool in recent years, especially for the mapping of risks to the spatial registration, consolidation, and prevention of losses in groundwater for the development of a groundwater information management system' in the sustainable management of groundwater resources (Papatheodorou et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater may be considered as one of the most precious and basic needs for human existence and the survival of mankind, providing us with luxuries and comforts in addition to fulfilling our basic necessities of life (Singh et al 2014). The deterioration of groundwater quality and the declining groundwater levels are the most pressing problems in many countries due to the increasing demands for water by increasing industrialization, population, urbanization and agricultural expansion (Neves & Matias 2008;Cidu et al 2009;Bhuiyan et al 2010;Verma & Singh 2013;Chandra et al 2015;Tiwari et al 2016;Verma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater levels represent the potentiometric state of water recharge, storage and discharge of the aquifer (Conlon et al 2005;Yu et al 2016). Groundwater-level fluctuation depends on several hydrogeological factors, such as geology, drainage, soil, slope, elevation and other parameters (Chandra et al 2015;Tiwari et al 2016). Recently, several studies have been concentrating on groundwater-level fluctuation, which is challenging to the scientific community working on hydrogeological factors and groundwater resource management (Bhuiyan 2010;Maggirwar et al 2011;Krishan et al 2014Krishan et al , 2016Chandra et al 2015;Yu et al 2016;Cai & Ofterdinger 2016;Tiwari et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation